A Possible Perspective about the Compositional Models, Evolution, and Clinical Meaning of Human Enterotypes - Francesco Di Pierro (Microorganisms, 2021)
Among the various parameters obtainable through the analysis of the human gut microbiota, the enterotype is one of the first classifications of the bacterial consortia, which tried to obtain, at the same time, as much information as possible to be applied in clinical medicine. Although some authors observed the existence not of clusters, but only of a real continuous gradient, enterotypes are commonly described according to various models. The first model predicted either clustering into enterotypes 1 and 2 based on two specific dominances, Bacteroides and Prevotella, respectively, with the Ruminococcus dominance blurred within the Bacteroides dominance, or it predicted a threedominant condition, in which the Ruminococcus driver constituted enterotype 3, separated from enterotype 1. A second model envisaged three possible ways to cluster gut microbiota, respectively centred on two, three, and four dominances. In the first case, enterotypes 1 and 2 coincided with the two original enterotypes, with the dominance of Bacteroides and Prevotella, respectively. In the second case, the existence of enterotype 3 was evident and whose dominance was not centred on Ruminococcus but extended more towards the entire Firmicutes phylum. In the third case, the presence of the phylum Firmicutes was split into two different enterotypes generating the clusters defined and named as Mixtures 1 and 2. Subsequently, the analysis of the water content (hydration) in the stool allowed the splitting of the Bacteroides enterotype into two sub-enterotype, respectively known as B1 and B2. All these models have allowed us to highlight some correlations between a specific enterotype, or cluster, and some characteristics, such as the greater predisposition of the respective hosts towards certain pathologies. These observations, coupled with the attempt to derive the different microbiota on an evolutionary basis, can help to shed new light on this topic and demonstrate the possible utility that the different ways of clustering the gut microbiota can have in a clinical application perspective and in preventive medicine.